Thermal performance of a novel dual-serpentine-channel flat-plate oscillating heat pipe used for multiple heat sources and sinks. (November 2020) - Liu, Xiangdong; Chen, Xi; Zhang, Ziwen; Chen, Yongping
Highlights: A novel dual-serpentine-channel flat-plate oscillating heat pipe (FPOHP) is designed and fabricated. Thermo-hydrodynamic characteristics of the FPOHP are experimentally investigated. FPOHP can work with uniform heating by multiple heat sources at center and air cooling at both ends. FPOHP has an equivalent thermal conductivity 5.8 times that of a pure 6063 aluminum alloy plate. FPOHP has a well gravity adaptability and thermal uniformity over wide operating conditions. Abstract: A novel dual-serpentine-channel flat-plate oscillating heat pipe (FPOHP) is designed and fabricated for electronic cooling with multiple heat sources and sinks. The FPOHP has two mirror symmetric tandem branches of capillary serpentine square channel with a hydraulic diameter of 2 mm (i.e., Bond number Bo = 1.137 1.265 here), which is made of 6063 aluminum alloy and 55% partially filled with acetone. A corresponding experimental study is conducted to investigate the start-up characteristics and quasi-steady thermal performance of the FPOHP with arrangement of "uniform heating by multiple heat sources at center and air cooling at both ends" under different inclination angles. The combined flow pattern diagrams as well as thermal resistance and equivalent thermal conductivity contour maps are provided for two mirror symmetric tandem sections of the FPOHP, based on which the thermo-hydrodynamic performance deviations between these two sections are compared and analyzed. The results show that the quasi-steady fluid motions in the FPOHP can be characterized by intermittent or independent occurrence of three elements, namely, stop, oscillation, and circulation, depending on the heat load and inclination angle. Significantly, the thermo-hydrodynamic behaviors in two tandem sections of the FPOHP both cooperate and compete with each other, as a result of the heat, mass and momentum exchanges via the tandem structure. The FPOHP can start up successfully under all inclination angles from 0° to 90° with no obvious difference, and its start-up temperature increases smoothly and approximately reaches a plateau of 41 46 °C as the heat load goes up. For the 175 tested conditions, the coefficients of variation for the thermal resistance of two tandem sections are smaller than 21.5% with the average value of 6.8%, showing a fine heat transfer uniformity of the FPOHP over a wide range of operating conditions. Significantly, in general, the FPOHP has much larger overall equivalent thermal conductivity (about 5.8 times on average) and possesses only a weight 83.6% of a pure 6063 aluminum alloy plate with the same geometry. In addition, the FPOHP exhibits a well gravity adaptability with the relative deviation ranging from 7.1% to 25.2% in the total thermal resistances for all inclination angles. Accordingly, the FPOHP shows a good potential for the high-heat-flux electronic cooling applications with multiple heat sources and sinks.